UNIQUENESS OF SOLUTION FOR A CLASS OF STEFAN PROBLEMS (Journal of Sciences, Islamic Republic of Iran)
This paper deals with a theoretical mathematical analysis of one-dimensional solidification problem, in which kinetic undercooling is incorporated into the This temperature condition at the interface. A model problem with nonlinear kinetic law is considered. We prove a local result intimate for the uniqueness of solution of the corresponding free boundary problem.